A Cohort Model and High Impact Practices in Undergraduate Public Health Education - Opacich, Karin Joann (Frontiers in Public Health, 2019)
Developing curriculum that is more than a collection of courses necessitates articulating philosophy and principles that undergird curricular decisions. While faculty are accustomed to expressing ideas within their realms of content expertise, building consensus around educational philosophy and pedagogy may be less common but equally important to assure coherent curriculum. Such discussions lead to intentional curriculum. When attuned to intent and combined with high impact practices, curriculum is likelier to result in student success and engagement. Since public health by nature entails community interaction, opportunities to think and work in a variety of communities reflects the work in the public health arena. Building a community of learners in the context of a highly diverse urban campus requires very deliberate curriculum planning and design. The likelihood that learning communities will emerge spontaneously is reduced when only a small proportion of students live on or near campus, and most spend considerable time commuting. Virtually all undergraduate public health students have responsibilities beyond academics, including employment, family caregiving, religious obligations, etc. Since most undergraduate students in this setting are first generation to higher education, learning communities and other high impact practices become even more important to provide meaningful baccalaureate education. Such communities evolve most efficiently when integrated into the curriculum design. By implementing a cohort model, not only can faculty participate and facilitate the evolution of a community of learners, they can employ other high impact practices designed to enhance and compound public health content and processes. Undergraduate public health students in this setting take all of their core courses (32 semester hours) together in a prescribed sequence. Faculty have clear understanding about what preceded a course and what follows. Every course entails both individual work and group collaboration. Students come to understand each other’s strengths and needs, and with rare exception, they support each other on the journey and share some mutual successes. Both expected and unintended outcomes of this approach are conveyed in this article along with a few cautions for those considering these strategies for undergraduate public health education.